Granulomatous epididymo-orchitis: diagnosis by fine needle aspiration. (January 2018) - Handa, Uma; Kundu, Reetu; Raghubanshi, Gunjan; Bhalla, Vidur
Tuberculosis is the leading cause of chronic granulomatous epididymo-orchitis in the Asian population. A retrospective analysis of 40 patients diagnosed with granulomatous or tubercular epididymo-orchitis on fine-needle aspiration (FNA) was carried out. May Grünwald giemsa, haematoxylin and eosin and Ziehl Neelsen stained smears were evaluated. Of 40 patients studied, aspiration smears showed epithelioid cell granulomas with caseation in 17, granulomas alone in 19 and caseation only in four. Acid fast bacilli were seen in 15. Cytologic diagnoses rendered were tubercular epididymo-orchitis in 15, granulomatous inflammation suggestive of tuberculosis in six and granulomatous inflammation in 19. FNA may readily diagnose tubercular epididymo-orchitis and may avoid unnecessary orchidectomy in a good number of patients.